Therapeutic Value of miRNAs in Coronary Artery Disease. (13th April 2021) - Ali Sheikh, Md Sayed; Alduraywish, A.; Almaeen, A.; Alruwali, Mubarak; Alruwaili, Raed; Alomair, Basil Mohammed; Salma, Umme; Hedeab, Gomaa Mostafa; Bugti, Najeebullah; A.M.Abdulhabeeb, Ibrahim
Abstract : Atherosclerotic ischemic coronary artery disease (CAD) is a significant community health challenge and the principal cause of morbidity and mortality in both developed and developing countries for all ethnic groups. The progressive chronic coronary atherosclerosis is the main underlying cause of CAD. Although enormous progress occurred in the last three decades in the management of cardiovascular diseases, the prevalence of CAD continues to increase worldwide, indicating the need for discovery of deeper molecular insights of CAD mechanisms, biomarkers, and innovative therapeutic targets. Recently, several research groups established that microRNAs essentially regulate various cardiovascular development and functions, and a deregulated cardiac enriched microRNA profile plays a vital role in the pathogenesis of CAD and its biological aging. Numerous studies established that over- or downregulation of a single miRNA gene by ago-miRNA or anti-miRNA is enough to modify the CAD disease process, significantly prevent age-dependent cardiac cell death, and markedly improve cardiac function. In the light of more recent experimental and clinical evidences, we briefly reviewed and discussed the involvement of miRNAs in CAD and their possible diagnostic/therapeutic values. Moreover, we also focused on the role of miRNAs in the initiation and progression of the atherosclerosis plaque as the strongest risk factor for CAD.